Body, capital, and screens : visual media and the healthy self in the 20th century - Bonah, Christian; Laukötter, Anja (MediaMatters., 2020)
Body, Capital and Screens' brings together new research from leading scholars from Europe and North America working at the intersection of film and media studies and social and cultural history of the body. The volume focuses on visual media in the twentieth century in Europe and the U.S. that informed and educated people about life and health as well as practices improving them. Through a series of in-depth case studies, the contributors to this volume investigate the relationships between film/television, private and public actors of the health sector and economic developments. The book explores the performative and interactive power of these visual media on individual health understandings, perceptions and practices. The book aims to better understand how bodily health has evolved as a form of capital throughout the century.